1973
DOI: 10.1007/bf01312593
|View full text |Cite
|
Sign up to set email alerts
|

A systems analysis of a campus community mental health facility: A preliminary investigation

Abstract: Faced with increasing demand and relatively static resources, community mental health facilities need to evaluate their functions in terms of time, cost, and performance effectiveness. For this study, the technology of systems analysis was applied to the functions of a progressive university counseling center. The systems analysis provided a management and information flow analysis and a time and cost analysis, as well as a performance analysis. This study focused on the preliminary results of the time, cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The concept of cost accounting in mental health settings is not new. Several authors have suggested the increasing necessity for cost accountability (Birnberg, 1976;O'Neil, Richardson, Carver, & Iscoe, 1973;Panzetta, 1973; Speilberger, Pincente, & Hobfoll, Note 1). Although several authors discuss cost accounting and cost analysis in general terms, the O'Neil et al study is considered by many as one of the few completed practical efforts dealing with cost and performance analysis in a mental health setting.…”
Section: Previous Cost Analysis Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of cost accounting in mental health settings is not new. Several authors have suggested the increasing necessity for cost accountability (Birnberg, 1976;O'Neil, Richardson, Carver, & Iscoe, 1973;Panzetta, 1973; Speilberger, Pincente, & Hobfoll, Note 1). Although several authors discuss cost accounting and cost analysis in general terms, the O'Neil et al study is considered by many as one of the few completed practical efforts dealing with cost and performance analysis in a mental health setting.…”
Section: Previous Cost Analysis Effortsmentioning
confidence: 99%
“…Actual cost calculations can be compared with budgeted costs for each program, thus providing a basis for determining whether objectives are being met with respect to cost figures. Indirectly, actual costs measure the degree to which actual effort and priorities match planned effort and priorities (O'Neil et al, 1973). This profile of time and cost data provides a base rate of staff effort in various activities and can be used proactively for future program and budget planning.…”
Section: Previous Cost Analysis Effortsmentioning
confidence: 99%